From Policy to Practice: Addressing SDG Challenges and Opportunities Through Social Sciences - Firman Maulana Rusdi; Arini Dwi Cahyani (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The achievement of Sustainable Development Goals (SDGs) presents various kinds of challenges and opportunities, especially in the context of social sciences. The purpose of this study is to examine the challenges and opportunities associated with implementing the SDGs from a social science approach. By analyzing relevant literature from 2020 to 2025, this study observes significant challenges such as policy inconsistencies, lack of inclusivity, and limited resources that obstruct effective implementation. In contrast, opportunities are identified in the form of interdisciplinary cooperation, technology developments, and the increasing focus on inclusive and equitable education. The findings show that social sciences play an important role in filling the gap between policy frameworks and practical applications, presenting innovative solutions to address complex societal issues. Furthermore, this study highlights the necessity of developing critical thinking, collaborative efforts, and adaptable solutions in order to overcome current obstacles and maximaze the potential of SDGs. Practical recommendations are provided to improve the efficiency of SDG-related projects which highlight the need for collaborative strategies and dynamic policy frameworks. Keywords: Sustainable Development Goals (SDGs), Social Sciences, Challenges, Opportunities, Interdisciplinary Collaboration